New nation: new history: the history workshop in South Africa 1979 - 1994 - Bonner, Phil (My University, 1994)
This article seeks to appraise the influence of the History Workshop (based at the University of the Witwatersrand in South Africa) both on the study of history in South Africa and on popular understandings of the past.
Paper presented at the Wits History Workshop: Democracy, Popular Precedents, Practice and Culture, 13-15 July, 1994.